Laparoscopic management of a newborn with a right Amyand's hernia and a left incarcerated inguinal hernia - Ciro Esposito; Marianna Iaquinto; Maria Escolino; Alessandro Settimi (Wolters Kluwer Medknow Publications, 2013)
A one month old boy presented with left incarcerated inguinal hernia. After unsuccessful manual reduction, we decided to perform laparoscopic herniorrhaphy. Laparoscopic examination showed a left hernia with intestinal loops that entered into the internal inguinal ring, on the right side there was an unknown patency of the peritoneal vaginal duct with the appendix completely incarcerated within the sac. On the left side, the loops were reduced with a combined technique of external manual pressure and internal pulling by forceps; the bowel was inspected, and the hernia was repaired. On the right side, the appendix was strongly adherent with the peritoneal vaginal duct, and the reduction was not possible. The appendix was dissected from the sac using a 3-mm monopolar hook and than reduced into the abdomen, then right herniorrhaphy was performed. Two days after surgery, the baby had fever and abdominal distension. He was re-operated through mini-Pfannenstiel incision and an ischemic appendix was identified and removed. Postoperative period was uneventful. In our case, laparoscopy allowed for simultaneous reduction under direct visual control, inspection of the incarcerated organ, definitive repair and incidentally discovery and treatment of the contralateral incarcerated Amyand's hernia. In case of incarcerated appendix, appendectomy is preferable during the same procedure to reduce the incidence of postoperative complications.